Preparation method of carbon movable sealing ring
By performing pyrolytic carbon deposition and chemical vapor deposition density enhancement treatment on the porous foam carbon matrix, the existing graphite materials have been solved under high temperature, high pressure and high speed conditions, and high density, high strength, low friction carbon dynamic sealing rings are prepared to meet the strict requirements of aerospace engines.
Patent Information
- Application Number
- CN202411983975.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing high-strength graphite materials face challenges in interaxial sealing applications of aerospace engines under the huge centrifugal force generated by high-speed rotation, and the development needs of liquid oxygen/kerosene engines put higher requirements on the performance of sealing materials.
The pyrolytic carbon deposition is used to prepare high-density and high-strength isotropic pyrolytic carbon blocks, and the density-enhancing treatment is reduced by chemical vapor deposition, and the number of surface micropores is improved, and the finish and service life are improved.
The preparation of high-performance carbon dynamic sealing ring is realized, meeting the performance requirements under high temperature, high pressure and high speed rotation conditions, reducing the preparation cost and equipment complexity.
Smart Images

Figure CN119751066A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon dynamic sealing rings, and in particular to a method for preparing a carbon dynamic sealing ring. Background Art
[0002] Aerospace engines work in extreme environments of high temperature, high pressure, high speed and high load, and the reliability of their sealing positions is crucial. The performance of sealing materials directly affects the flight safety of rockets, the service life of components and the stability of the system. As the core component of the engine, the sealing material must withstand extreme temperature changes, high pressure, microgravity and corrosion, and at the same time have the characteristics of high strength, high oxidation resistance, high temperature resistance, good thermal conductivity and stable low friction coefficient. Graphite materials are widely used in dynamic sealing components of aerospace engines due to their light weight, high thermal conductivity, low friction coefficient, high temperature resistance and self-lubrication.
[0003] However, existing high-strength graphite materials have encountered challenges in the application of aerospace engine shaft seals, especially under the huge centrifugal force generated by high-speed rotation, which puts higher requirements on the tensile strength and friction and wear performance of sealing materials. At the same time, the development needs of liquid oxygen / kerosene engines have further intensified the requirements for the performance of sealing materials, including low open porosity, high strength, high hardness and impact resistance. Therefore, the development of higher-performance pyrolytic carbon sealing materials to meet these stringent requirements has become one of the key tasks in the development of liquid oxygen / kerosene engines.
[0004] The existing carbon dynamic seal ring material preparation process usually uses ultrafine isotropic graphite powder with a particle size of no more than 1μm and high melting point asphalt or resin as raw materials, and is prepared by high temperature and high pressure isostatic pressing technology. This not only places high demands on raw materials, but also requires high difficulty in preparing the required ultrafine graphite particles. It also has strict requirements on equipment and is not suitable for the manufacture of special-shaped components. In response to these problems, the present invention proposes a method for preparing a carbon dynamic seal ring, that is, pyrolytic carbon deposition is performed on a porous foam carbon matrix to prepare a high-density, high-strength isotropic pyrolytic carbon block, which is then processed into a highly wear-resistant dynamic seal ring component. This method does not require ultrafine graphite powder as a raw material, and eliminates the isostatic pressing process, thereby significantly reducing the preparation cost. Summary of the invention
[0005] In view of the defects of the above-mentioned prior art, the object of the present invention is to provide a method for preparing a carbon dynamic sealing ring.
[0006] To achieve the above object, the present invention provides a method for preparing a carbon dynamic seal ring, comprising the following steps:
[0007] Step 1: crush the mesophase asphalt, then put the crushed asphalt into a mold, and then put the mold into a foaming reaction device for foaming treatment. After the foaming is completed, cool it to room temperature to obtain an asphalt-based foamed carbon precursor;
[0008] Step 2: Carbonizing the obtained asphalt-based foamed carbon precursor in a high-temperature carbonization furnace under the protection of a nitrogen atmosphere for 4-6 hours to obtain an asphalt foamed carbon template;
[0009] Step 3: Cut the asphalt foam carbon template according to the required size of the dynamic sealing ring to obtain a preform for deposition, and then perform surface activation treatment on the preform;
[0010] Step 4: subjecting the carbon foam preform that has undergone surface activation treatment to chemical vapor deposition densification treatment in a deposition furnace;
[0011] Step 5: Mechanically process the deposited and densified original blank according to the required dynamic sealing ring size to obtain an annular carbon dynamic sealing ring with uniform texture.
[0012] Furthermore, in the step three, the specific operation of the surface activation treatment is: soaking the preform in deionized water, then ultrasonically cleaning to remove dust in the pores of the preform, then soaking the cleaned preform in a nitric acid solution, and heating the solution to 60-80°C and maintaining it for 1-3 hours, and finally cleaning the preform with deionized water and drying it for standby use.
[0013] Furthermore, in the step one, the specific operation of the foaming treatment is: first, the temperature is raised to 230-270°C at a heating rate of 3-8°C / min, and then nitrogen is introduced to raise the pressure in the kettle to 2.8-3.3MPa, and then the temperature is raised to 430-460°C at a heating rate of 1-3°C / min, and kept warm for 3-5 hours. In the step four, natural gas is used as the carbon source gas for deposition densification, and an argon-hydrogen mixture is used as the carrier gas.
[0014] Furthermore, during the preparation of the asphalt-based foamed carbon precursor, the asphalt is crushed to 80-120 mesh before foaming to improve the foaming effect and uniformity of the asphalt. The asphalt crushing process adopts mechanical crushing or ultrasonic crushing technology. The foaming reaction device is an autoclave to ensure that the asphalt can be fully foamed under high temperature and high pressure conditions. The inner wall of the autoclave is made of corrosion-resistant materials to improve the service life and safety of the equipment, such as special ceramics or alloys to extend the service life of the furnace body. The autoclave adopts a multi-layer insulation setting to reduce external heat loss and protect operators from high temperature injuries.
[0015] Furthermore, during the carbonization process of the asphalt foam carbon template, the carbonization temperature is 900-1100°C to ensure the carbonization effect and quality of the asphalt foam carbon template, the high-temperature carbonization furnace adopts a program temperature control system to accurately control the carbonization temperature and time, and during the surface activation treatment of the foam carbon preform, the ultrasonic cleaning time is 15-30 minutes to ensure that the dust in the pores of the preform is effectively removed, the ultrasonic cleaning equipment adopts a frequency-adjustable ultrasonic generator to adapt to preforms with different pore sizes, the concentration of the nitric acid solution is 35%-70% to ensure the activation effect of the preform surface, and the nitric acid solution adopts a circulating heating system to maintain the uniformity of the solution temperature.
[0016] Furthermore, during the chemical vapor deposition densification process, under normal pressure or slightly positive pressure, the deposition temperature is 1500-1700°C to ensure the densification effect and quality of the foam carbon preform. The deposition furnace adopts multi-zone temperature control technology to achieve temperature gradient control during the deposition process. The ratio of the carbon source gas to the carrier gas is Vcarbon source gas: Vcarrier gas = 0.1-0.15 to ensure the uniformity and efficiency of the deposition densification. The carbon source gas and the carrier gas adopt a precise flow control system to ensure the accuracy of the gas ratio. During the chemical vapor deposition densification process, the deposition time is 50-80 hours to ensure that the density of the foam carbon preform reaches 1.85g / cm3. The deposition time is monitored and adjusted by the control system to improve the deposition efficiency and product quality.
[0017] Furthermore, the process further includes an environmental monitoring step, a quality control step and a data recording and analysis step. The quality control step involves quality inspection of intermediate products after each preparation stage to ensure the quality and performance of the final product. The environmental monitoring step involves real-time monitoring and control of environmental conditions, such as humidity and temperature, during the preparation process to ensure the stability of the preparation process and the consistency of the product. The data recording and analysis step involves recording all parameters and conditions in the preparation process and using data analysis technology to optimize the preparation process, improve efficiency and product quality, including data acquisition, data preprocessing and data analysis. First, it is necessary to collect all parameter and condition data related to the preparation process. After the raw data is collected, data processing and organization are performed to eliminate outliers, missing values and duplicate data to ensure the quality and accuracy of the data. Statistical analysis, machine learning and other methods are used to conduct in-depth analysis of the data, extract useful patterns and trends from the cleaned data, and predict future behavior through mathematical models.
[0018] Furthermore, in the step 2, carbonization is carried out in a high-temperature carbonization furnace under the protection of a nitrogen atmosphere. The use of a nitrogen atmosphere can effectively isolate oxygen to prevent the asphalt foam carbon template from oxidizing at high temperatures, which would lead to a decrease in material properties. The system is equipped with a nitrogen purity monitoring device to ensure that the purity of the nitrogen entering the autoclave reaches more than 99.99% to minimize the risk of oxidation. The carbonization furnace is equipped with an air pressure regulating system, which includes an air pressure sensor and an electric valve, which can accurately control the pressure in the furnace during the carbonization process to ensure the uniform distribution and stability of the nitrogen atmosphere. The air pressure sensor in the carbonization furnace can accurately measure the pressure changes during the carbonization process to ensure the accuracy of pressure control and allow the user to set safety limits for the air pressure. Once these limits are exceeded, the system will automatically take measures, such as opening the electric valve to discharge the gas to release the pressure. At the same time, it is equipped with an integrated alarm system to emit an audible and visual alarm when the air pressure exceeds the preset range to remind the operator to take corresponding measures.
[0019] Furthermore, a carbon dynamic seal ring is obtained by the preparation technology described in any one of claims 1 to 8, and the dynamic seal ring has the following characteristics: the volume density reaches 1.85g / cm 3 The surface open porosity is less than 0.1%, the compressive strength is greater than 360MPa, and the friction coefficient is less than 0.1, which meets the performance requirements of high-temperature carbon dynamic sealing rings.
[0020] Furthermore, during the preparation process of the dynamic sealing ring, the foaming conditions and carbonization conditions of the asphalt-based foamed carbon precursor are controlled to achieve microstructural regulation of the dynamic sealing ring. Through chemical vapor deposition densification treatment, the number of micropores on the surface of the dynamic sealing ring is significantly reduced, and the surface smoothness of the dynamic sealing ring after polishing is improved, thereby reducing its friction coefficient and increasing its service life. The dynamic sealing ring adopts a porous foamed carbon matrix for deposition densification. The ultra-high open porosity and specific surface area accelerate the rate of chemical vapor deposition densification. The density can reach 1.85g / cm3 in only 60 hours, thereby improving the preparation efficiency.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The present invention proposes a new process for preparing a carbon dynamic seal ring. By combining a porous carbon foam preform with atmospheric pressure chemical vapor deposition densification, a high-performance carbon dynamic seal ring is successfully prepared, ensuring that the product meets the requirements of a high-temperature carbon dynamic seal ring in terms of physical properties, mechanical properties and friction properties.
[0023] 2. The chemical vapor deposition densification method adopted in the present invention significantly reduces the number of micropores on the surface of the dynamic sealing ring, which helps to improve the smoothness of the polished surface, thereby reducing the friction coefficient and increasing the service life.
[0024] 3. The advantage of the present invention of using a porous foam carbon matrix for deposition densification is its ultra-high open porosity and specific surface area, which greatly accelerates the rate of chemical vapor deposition. In addition, the processability of the foam carbon matrix allows it to be processed into any desired shape, providing greater design flexibility.
[0025] 4. Compared with the hot isostatic pressing process, the atmospheric pressure chemical vapor deposition process of the present invention is simpler in equipment, has a shorter preparation cycle, and has no special requirements for raw materials, which greatly reduces the cost of raw materials. Therefore, the present invention not only has significant practicality and economic value, but also provides a new idea and method for the preparation of carbon dynamic sealing rings.
[0026] 5. In the carbonization process of the present invention, the use of nitrogen atmosphere protection can effectively isolate oxygen and prevent the asphalt foam carbon template from being oxidized at high temperature, thereby improving the safety and reliability of the material.
[0027] In response to the demand for high-end carbon dynamic sealing materials in the aerospace field, the present invention innovatively proposes a simple, economical and practical carbon dynamic sealing ring preparation process, which significantly improves the service life of the material and effectively overcomes the problems of long preparation cycle, high cost, short life and unstable quality of existing materials; in addition, the process uses ordinary asphalt or resin as raw materials, which significantly reduces costs compared to the ultrafine powder graphite isostatic pressing process used in Europe and the United States. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the scheme in the present invention, a brief introduction is given below to the drawings required for use in the description of the embodiments of the present invention. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0029] Figure 1 It is a schematic diagram of the process provided by the present invention. DETAILED DESCRIPTION
[0030] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more explicit definition of the protection scope of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention.
[0031] The terms "including" and "having" and any variations thereof in the specification and claims of the present invention and the above-mentioned drawings are intended to cover non-exclusive inclusions. The terms "first", "second", etc. in the specification and claims of the present invention or the above-mentioned drawings are used to distinguish different objects rather than to describe a specific order.
[0032] See also Figure 1 , a method for preparing a carbon dynamic sealing ring, comprising the following steps:
[0033] Step 1: crush the mesophase asphalt, then put the crushed asphalt into a mold, and then put the mold into a foaming reaction device for foaming treatment. After the foaming is completed, cool it to room temperature to obtain an asphalt-based foamed carbon precursor;
[0034] Step 2: Carbonizing the obtained asphalt-based foamed carbon precursor in a high-temperature carbonization furnace under the protection of a nitrogen atmosphere for 4-6 hours to obtain an asphalt foamed carbon template;
[0035] Step 3: Cut the asphalt foam carbon template according to the required size of the dynamic sealing ring to obtain a preform for deposition, and then perform surface activation treatment on the preform;
[0036] Step 4: subjecting the carbon foam preform that has undergone surface activation treatment to chemical vapor deposition densification treatment in a deposition furnace;
[0037] Step 5: Mechanically process the deposited and densified original blank according to the required dynamic sealing ring size to obtain an annular carbon dynamic sealing ring with uniform texture.
[0038] In step three, the specific operation of the surface activation treatment is: soak the preform in deionized water, then ultrasonically clean it to remove dust in the pores of the preform, then soak the cleaned preform in a nitric acid solution, and heat the solution to 60-80°C and keep it for 1-3 hours, and finally clean the preform with deionized water and dry it for use.
[0039] In step one, the specific operation of the foaming treatment is: first, increase the temperature to 230-270°C at a heating rate of 3-8°C / min, then introduce nitrogen to increase the pressure in the kettle to 2.8-3.3MPa, and then increase the temperature to 430-460°C at a heating rate of 1-3°C / min, and keep warm for 3-5 hours. In step four, natural gas is used as the carbon source gas for deposition densification, and argon-hydrogen mixed gas is used as the carrier gas.
[0040] In step 1, the porous carbon foam precursor can be foamed with mesophase asphalt, high melting point asphalt, phenolic resin and other high molecular compounds; in step 3, the carbon foam surface activation treatment can be oxidized with nitric acid, sulfuric acid, hydrogen peroxide and other oxides; in step 4, the chemical vapor deposition densification can use natural gas as the carbon source gas, as well as propylene, propane and other carbon source gases.
[0041] As an improvement of the above technical solution, in the preparation process of the asphalt-based foamed carbon precursor, the asphalt is crushed to 80-120 mesh before foaming to improve the foaming effect and uniformity of the asphalt. The asphalt crushing process adopts mechanical crushing or ultrasonic crushing technology. The foaming reaction device is an autoclave to ensure that the asphalt can be fully foamed under high temperature and high pressure conditions. The inner wall of the autoclave is made of corrosion-resistant materials to improve the service life and safety of the equipment, such as special ceramics or alloys to extend the service life of the furnace body. The autoclave adopts a multi-layer insulation setting to reduce external heat loss and protect operators from high temperature damage.
[0042] As an improvement of the above technical solution, during the carbonization process of the asphalt foam carbon template, the carbonization temperature is 900-1100°C to ensure the carbonization effect and quality of the asphalt foam carbon template. The high-temperature carbonization furnace adopts a program temperature control system to accurately control the carbonization temperature and time. During the surface activation treatment of the foam carbon preform, the ultrasonic cleaning time is 15-30 minutes to ensure that the dust in the pores of the preform is effectively removed. The ultrasonic cleaning equipment uses a frequency-adjustable ultrasonic generator to adapt to preforms with different pore sizes. The concentration of the nitric acid solution is 35%-70% to ensure the activation effect of the preform surface. The nitric acid solution adopts a circulating heating system to maintain the uniformity of the solution temperature.
[0043] As an improvement of the above technical solution, during the chemical vapor deposition densification process, under normal pressure or slightly positive pressure, the deposition temperature is 1500-1700°C to ensure the densification effect and quality of the foam carbon preform. The deposition furnace adopts multi-zone temperature control technology to achieve temperature gradient control during the deposition process. The ratio of carbon source gas to carrier gas is Vcarbon source gas: Vcarrier gas = 0.1-0.15 to ensure the uniformity and efficiency of deposition densification. The carbon source gas and carrier gas adopt a precise flow control system to ensure the accuracy of the gas ratio. During the chemical vapor deposition densification process, the deposition time is 50-80 hours to ensure that the density of the foam carbon preform reaches 1.85g / cm3. The deposition time is monitored and adjusted by the control system to improve deposition efficiency and product quality.
[0044] As an improvement of the above technical solution, the process further includes an environmental monitoring step, a quality control step and a data recording and analysis step. The quality control step involves quality inspection of intermediate products after each preparation stage to ensure the quality and performance of the final product. The environmental monitoring step involves real-time monitoring and control of environmental conditions such as humidity and temperature during the preparation process to ensure the stability of the preparation process and the consistency of the product. The data recording and analysis step involves recording all parameters and conditions in the preparation process and using data analysis technology to optimize the preparation process, improve efficiency and product quality, including data acquisition, data preprocessing and data analysis. First, it is necessary to collect all parameter and condition data related to the preparation process. After collecting the raw data, data processing and organization are performed to eliminate outliers, missing values and duplicate data to ensure the quality and accuracy of the data. Statistical analysis, machine learning and other methods are used to conduct in-depth analysis of the data, extract useful patterns and trends from the cleaned data, and predict future behavior through mathematical models.
[0045] As an improvement of the above technical solution, in step 2, a high-temperature carbonization furnace under the protection of a nitrogen atmosphere is used for carbonization. The use of nitrogen atmosphere protection can effectively isolate oxygen to prevent the asphalt foam carbon template from oxidizing at high temperature, resulting in a decrease in material performance. The system is equipped with a nitrogen purity monitoring device to ensure that the purity of the nitrogen entering the carbonization furnace reaches more than 99.99% to minimize the risk of oxidation. The carbonization furnace is equipped with an air pressure regulating system. The air pressure regulating system includes an air pressure sensor and an electric valve, which can accurately control the pressure in the furnace during the carbonization process to ensure the uniform distribution and stability of the nitrogen atmosphere. The air pressure sensor in the carbonization furnace can accurately measure the pressure changes during the carbonization process to ensure the accuracy of pressure control and allow the user to set safety limits for the air pressure. Once these limits are exceeded, the system will automatically take measures, such as opening the electric valve to discharge the gas to release the pressure. At the same time, it is equipped with an integrated alarm system to emit an audible and visual alarm when the air pressure exceeds the preset range to remind the operator to take corresponding measures.
[0046] As an improvement of the above technical solution, a carbon dynamic sealing ring is obtained by the preparation technology of any one of claims 1 to 8, and the dynamic sealing ring has the following characteristics: the volume density reaches 1.85g / cm3, the surface open pore porosity is less than 0.1%, the compressive strength is greater than 360MPa, and the friction coefficient is less than 0.1, which meets the performance requirements of high-temperature carbon dynamic sealing rings. During the preparation process of the dynamic sealing ring, the microstructure of the dynamic sealing ring is regulated by controlling the foaming conditions and carbonization conditions of the asphalt-based foam carbon precursor. Through chemical vapor deposition densification treatment, the number of micropores on the surface of the dynamic sealing ring is significantly reduced, and the smoothness of the surface of the dynamic sealing ring after polishing is improved, thereby reducing its friction coefficient and increasing its service life. The dynamic sealing ring adopts a porous foam carbon matrix for deposition densification. The ultra-high open porosity and specific surface area accelerate the rate of chemical vapor deposition densification. The density can reach 1.85g / cm3 in only 60 hours, thereby improving the preparation efficiency.
[0047] Working principle and use method of the present invention:
[0048] Working principle:
[0049] Preparation of asphalt-based foamed carbon precursor: The mesophase asphalt is crushed to 80-120 meshes by mechanical crushing or ultrasonic crushing technology to improve the foaming effect and uniformity, and the crushed asphalt is placed in a mold, and then the mold is placed in an autoclave for foaming. During the foaming process, the temperature is first raised to 230-270°C at a heating rate of 3-8°C / min, and then nitrogen is introduced to raise the pressure in the autoclave to 2.8-3.3MPa, and then the temperature is raised to 430-460°C at a heating rate of 1-3°C / min. After keeping the temperature for 3-5 hours, it is cooled to room temperature to obtain an asphalt-based foamed carbon precursor.
[0050] Carbonization process: The asphalt-based foamed carbon precursor is carbonized in a high-temperature carbonization furnace under the protection of a nitrogen atmosphere at a carbonization temperature of 900-1100° C. for 4-6 hours to obtain an asphalt foamed carbon template.
[0051] Surface activation treatment: according to the required size of the dynamic sealing ring, the asphalt foam carbon template is cut to obtain a preform for deposition, and the preform is subjected to surface activation treatment, including soaking in deionized water, ultrasonic cleaning for 15-30 minutes to remove dust, and then soaking in 35%-70% nitric acid solution, heating to 60-80°C for 1-3 hours, and finally washing with deionized water and drying for standby use.
[0052] Chemical vapor deposition densification treatment: The foam carbon preform that has undergone surface activation treatment is subjected to chemical vapor deposition densification treatment in a deposition furnace, the deposition temperature is 1500-1700°C, natural gas is used as the carbon source gas, argon hydrogen mixed gas is used as the carrier gas, V carbon source gas: V carrier gas = 0.1-0.15, and the deposition time is 50-80 hours.
[0053] Machining: The deposited and densified original blank is machined according to the required dynamic sealing ring size to obtain an annular carbon dynamic sealing ring with uniform texture.
[0054] Directions:
[0055] Prepare raw materials: Prepare mesophase asphalt and crush it to appropriate particle size as needed.
[0056] Foaming treatment: Place the crushed asphalt into a mold and perform foaming treatment in an autoclave, strictly following the above temperature and pressure conditions.
[0057] Carbonization: Carry out carbonization under nitrogen protection, and control the carbonization temperature and time to ensure the quality of the asphalt foam carbon template.
[0058] Cutting and activation treatment: According to the required size of the dynamic seal ring, the carbon template is cut into appropriate sizes and subjected to surface activation treatment, including cleaning and chemical treatment.
[0059] Chemical Vapor Deposition: Chemical vapor deposition densification is carried out in a deposition furnace, controlling the deposition temperature, gas ratio and deposition time.
[0060] Machining and quality inspection: The deposited and densified blank is machined to produce the final carbon dynamic seal ring, and the intermediate product is quality inspected after each preparation stage to ensure the performance and quality of the final product.
[0061] Environmental monitoring and data recording: During the entire preparation process, environmental conditions are monitored and controlled in real time, and all parameters and conditions are recorded, using data analysis technology to optimize the preparation process.
[0062] Example
[0063] Purpose: To prepare a batch of carbon dynamic seal rings with long service life for use in the sealing position of aerospace engines.
[0064] Raw materials and equipment preparation:
[0065] Mesophase pitch: As the main raw material, mesophase pitch suitable for high temperature applications is selected.
[0066] This asphalt needs to have a high aromaticity and a suitable H / C atomic ratio to ensure that it can be well converted during the preparation process.
[0067] Deionized water: used to clean the preform to ensure that it is free of impurities.
[0068] The resistivity of deionized water must be greater than 0.5MΩ·cm, and can reach up to 18MΩ, ensuring that its purity is higher than that of distilled water, and is suitable for cleaning preforms to prevent contamination by impurities.
[0069] Nitric acid: concentration of 50%, used for surface activation treatment of preforms.
[0070] Select nitric acid of superior grade (GR) or analytical grade (AR) with purity of 99.8% and 99.7% respectively to ensure the effect of surface activation treatment.
[0071] Natural gas, argon, and hydrogen: used as carbon source gas and carrier gas for chemical vapor deposition.
[0072] High-pressure autoclave: used for asphalt foaming treatment, the inner wall is made of special ceramic materials and has a multi-layer heat insulation setting.
[0073] High temperature carbonization furnace: equipped with a programmable temperature control system, used for the carbonization of asphalt-based foam carbon precursors.
[0074] Ultrasonic cleaner: frequency is adjustable, used for surface cleaning of preforms.
[0075] Deposition furnace: Equipped with multi-zone temperature control technology for chemical vapor deposition densification processes.
[0076] CNC machine tools: used for final machining to ensure dimensional accuracy.
[0077] Nitrogen purity monitoring device, air pressure regulating system, air pressure sensor: used to ensure nitrogen atmosphere during the carbonization process.
[0078] Detailed steps:
[0079] Preparation of pitch-based carbon foam precursor:
[0080] The intermediate phase asphalt is crushed into 100 mesh, and the crushed asphalt is placed in a mold using a mechanical crushing technology. The mold is then placed in an autoclave, and the temperature is raised to 250°C at a heating rate of 5°C / min. Nitrogen is introduced to raise the pressure in the autoclave to 3.0 MPa, and the temperature is raised to 450°C at a heating rate of 2°C / min. The mixture is kept warm for 4 hours, and then cooled to room temperature to obtain an asphalt-based foamed carbon precursor.
[0081] Use mechanical crushing technology to crush the mesophase asphalt to 100 mesh to improve the foaming effect and uniformity. During the crushing process, attention should be paid to protecting the safety of surrounding facilities and pipelines, and ensuring that the crushed asphalt will not pollute the surrounding environment.
[0082] Carbonization process:
[0083] The asphalt-based foamed carbon precursor was carbonized in a high-temperature carbonization furnace under the protection of a nitrogen atmosphere. The carbonization temperature was 1000°C and the temperature was kept constant for 6 hours. A nitrogen purity monitoring device was used to ensure that the nitrogen purity reached 99.99%. The pressure in the furnace was accurately controlled using a gas pressure regulating system and a gas pressure sensor.
[0084] Cutting and surface activation:
[0085] According to the required size of the dynamic sealing ring, the asphalt foam carbon template is cut into a preform for deposition, the preform is soaked in deionized water, and then ultrasonically cleaned for 20 minutes to remove dust in the holes, the cleaned preform is soaked in 50% nitric acid solution, heated to 70°C for 2 hours, and finally the preform is cleaned with deionized water and dried for standby use.
[0086] Chemical Vapor Deposition Densification Treatment:
[0087] The foam carbon preform that has undergone surface activation treatment is subjected to chemical vapor deposition densification treatment in a deposition furnace. The deposition temperature is 1600°C, natural gas is used as the carbon source gas, argon-hydrogen mixed gas is used as the carrier gas, Vcarbon source gas: Vcarrier gas=0.12, and the deposition time is 70 hours. A precise flow control system is used to ensure the accuracy of the gas ratio. The control system monitors and adjusts the deposition time.
[0088] Machining:
[0089] The deposited and densified original blank is machined according to the required dynamic seal ring size by using a CNC machine tool to obtain an annular carbon dynamic seal ring with uniform texture.
[0090] Quality testing and environmental monitoring:
[0091] The intermediate products are quality tested after each preparation stage, including the determination of bulk density, surface open porosity, compressive strength and friction coefficient. Environmental conditions such as humidity and temperature are monitored and controlled in real time, and all parameters and conditions are recorded. Data analysis technology is used to optimize the preparation process.
[0092] Result analysis:
[0093] Through the above steps, a batch of carbon dynamic seal rings were successfully prepared, with a volume density of 1.85g / cm1, a surface open porosity of less than 0.1%, a compressive strength greater than 360MPa, and a friction coefficient less than 0.1, meeting the performance requirements of high-temperature carbon dynamic seal rings. In addition, by controlling the foaming and carbonization conditions of the asphalt-based foam carbon precursor, the microstructure of the dynamic seal ring is regulated. Through chemical vapor deposition densification treatment, the number of micropores on the surface of the dynamic seal ring is significantly reduced, and the surface finish of the dynamic seal ring after polishing is improved, thereby reducing its friction coefficient and increasing its service life. The whole process embodies the characteristics of simple operation, economical and practical, and excellent performance, and has great practicality and economic value.
[0094] The above description is only used to illustrate the technical solution of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, it should be understood by those skilled in the art that the technical solution described in the aforementioned embodiments can still be modified, or some or all of the technical features therein can be replaced by equivalents. Any equivalent structure or equivalent process transformation made using the contents of the specification and drawings of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a carbon dynamic seal ring, characterized in that: The following steps are involved: Step 1: crush the mesophase asphalt, then put the crushed asphalt into a mold, and then put the mold into a foaming reaction device for foaming treatment. After the foaming is completed, cool it to room temperature to obtain an asphalt-based foamed carbon precursor; Step 2: Carbonizing the obtained asphalt-based foamed carbon precursor in a high-temperature carbonization furnace under the protection of a nitrogen atmosphere for 4-6 hours to obtain an asphalt foamed carbon template; Step 3: Cut the asphalt foam carbon template according to the required size of the dynamic sealing ring to obtain a preform for deposition, and then perform surface activation treatment on the preform; Step 4: subjecting the carbon foam preform that has undergone surface activation treatment to chemical vapor deposition densification treatment in a deposition furnace; Step 5: Mechanically process the deposited and densified original blank according to the required dynamic sealing ring size to obtain an annular carbon dynamic sealing ring with uniform texture.
2. A method for preparing a carbon dynamic seal ring according to claim 1, characterized in that: In the step three, the specific operation of the surface activation treatment is: soaking the preform in deionized water, then ultrasonically cleaning to remove dust in the pores of the preform, then soaking the cleaned preform in a nitric acid solution, and heating the solution to 60-80°C and maintaining it for 1-3 hours, and finally cleaning the preform with deionized water and drying it for standby use.
3. A method for preparing a carbon dynamic seal ring according to claim 1, characterized in that: In the step one, the specific operation of the foaming treatment is: first, the temperature is raised to 230-270°C at a heating rate of 3-8°C / min, then nitrogen is introduced to raise the pressure in the kettle to 2.8-3.3MPa, and then the temperature is raised to 430-460°C at a heating rate of 1-3°C / min, and kept warm for 3-5 hours. In the step four, natural gas is used as the carbon source gas for deposition densification, and an argon-hydrogen mixture is used as the carrier gas.
4. A method for preparing a carbon dynamic seal ring according to claim 2, characterized in that: During the preparation of the asphalt-based foamed carbon precursor, the asphalt is crushed to 80-120 meshes before foaming, and the asphalt crushing process adopts mechanical crushing or ultrasonic crushing technology. The foaming reaction device is an autoclave, the inner wall of the autoclave is made of corrosion-resistant material, and the autoclave adopts a multi-layer insulation setting.
5. A method for preparing a carbon dynamic seal ring according to claim 4, characterized in that: During the carbonization process of the asphalt foam carbon template, the carbonization temperature is 900-1100° C., the high-temperature carbonization furnace adopts a program temperature control system, during the surface activation treatment of the foam carbon preform, the ultrasonic cleaning time is 15-30 minutes, the ultrasonic cleaning equipment adopts a frequency-adjustable ultrasonic generator, the concentration of the nitric acid solution is 35%-70%, and the nitric acid solution adopts a circulating heating system.
6. A method for preparing a carbon dynamic seal ring according to claim 3, characterized in that: During the chemical vapor deposition densification process, under normal pressure or slightly positive pressure, the deposition temperature is 1500-1700°C, the deposition furnace adopts multi-zone temperature control technology, the ratio of the carbon source gas to the carrier gas is Vcarbon source gas: Vcarrier gas=0.1-0.15, and the carbon source gas and the carrier gas adopt a precise flow control system. During the chemical vapor deposition densification process, the deposition time is 50-80 hours, and the deposition time is monitored and adjusted by the control system.
7. A method for preparing a carbon dynamic seal ring according to claim 1, characterized in that: The process further includes an environmental monitoring step, a quality control step and a data recording and analysis step. The quality control step involves quality inspection of intermediate products after each preparation stage, the environmental monitoring step involves real-time monitoring and control of environmental conditions during the preparation process, and the data recording and analysis step involves recording all parameters and conditions in the preparation process and using data analysis technology to optimize the preparation process, including data acquisition, data preprocessing and data analysis. First, it is necessary to collect all parameter and condition data related to the preparation process. After collecting the original data, data processing and organization are performed to eliminate outliers, missing values and duplicate data to ensure the quality and accuracy of the data. Statistical analysis, machine learning and other methods are used to conduct in-depth analysis of the data, extract useful patterns and trends from the cleaned data, and use mathematical models to predict future behaviors.
8. The method for preparing a carbon dynamic seal ring according to claim 1, characterized in that: In the step 2, the system is equipped with a nitrogen purity monitoring device, and the autoclave is equipped with a gas pressure regulating system, which includes a gas pressure sensor and an electric valve.
9. A carbon dynamic seal ring, characterized in that: The dynamic sealing ring is obtained by the preparation technology described in any one of claims 1 to 8, and has the following characteristics: the volume density reaches 1.85g / cm3, the surface open pore porosity is less than 0.1%, the compressive strength is greater than 360MPa, and the friction coefficient is less than 0.
1.
10. The carbon dynamic seal ring according to claim 9, characterized in that: During the preparation process of the dynamic sealing ring, the foaming conditions and carbonization conditions of the asphalt-based foamed carbon precursor are controlled to achieve microstructural regulation of the dynamic sealing ring. The number of micropores on the surface of the dynamic sealing ring is significantly reduced through chemical vapor deposition densification treatment. The dynamic sealing ring uses a porous foamed carbon matrix for deposition densification.
Citation Information
Patent Citations
Method for preparing pitch-based foam carbon
CN101927996A
Method for preparing graphitized foam carbon by using boron-based catalyst
CN103626153A
Preparation of novel copper-plating foam carbon
CN104498917A
Method and system for preparing large cylindrical carbon-carbon thermal field material in multi-stock-column short-period mode through CVI (Chemical Vapor Infiltration) system
CN115636685A
Preparation method and application of hydrophilic integral foam carbon
CN118637615A